Pembelajaran Berbasis Pengalaman (Experiential Learning) dalam Menumbuhkan Empati (Cinta Sesama) di Pondok Pesantren Al-Khairiyah - Debi Tiara Wulan Dari; Ahmad Zainuri; Muslim Gani Yasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Empathy, as an aspect of social care, is a central component of character education in Islamic boarding schools. This study aims to explore how experiential learning fosters empathy among students at Pondok Pesantren Al-Khairiyah and to provide recommendations for developing character education based on experience aligned with Islamic values. The study employed a qualitative approach using participatory observation, documentation, and field notes. Data were analyzed using content analysis, including data reduction, thematic categorization, and conceptual synthesis. Results indicate that students’ involvement in cooperative activities, maintaining cleanliness of classrooms, dormitories, kitchens, mosques, and schoolyards, as well as participating in social tasks, strengthens the internalization of empathy. Post-activity reflection and the modeling behavior of teachers further reinforce character development. These activities also foster ecological awareness and collective responsibility, in line with the maslahah principle in Islamic education. All experiential learning activities are part of a curriculum of love, emphasizing care, empathy, and moral-social values, while strengthening social relations among students. The study confirms that experiential learning, when integrated with moral and spiritual values, effectively builds empathy as a foundation of holistic character. Findings provide practical insights for developing experience-based character education in pesantrens and other Islamic educational institutions.